From floppy disks to AI tutors: technology changes, human guidance endures - Hashim, Norhafizah; Abdul Rahman, Normaziah; Aziz Fadzillah, Nor Azlina; Yusof, Rozianiwati; Mohd Yunus, Sri Yusmawati (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Learning programming in the late 1990s relied on bulky desktops, limited internet access, and printed manuals, with C commonly taught as the first language. Today, AI tools like ChatGPT and GitHub Copilot, along with platforms such as Coursera and Udemy, offer personalised, self-paced learning and rapid coding assistance. However, in a fast-changing VUCA environment marked by volatility, uncertainty, complexity, and ambiguity students must navigate constantly evolving tools, uncertain skill demands, and an overwhelming array of online resources, which can be both empowering and disorienting.